The precise and accurate determination of thallium isotope compositions and concentrations for water samples by MC-ICPMS - Nielsen, S; Rehkamper, M; Baker, J; Halliday, A (2004)
We present optimised analytical protocols for the precise and accurate determination of Tl concentrations and isotope compositions (IC) for water samples by multiple collector inductively coupled plasma mass spectrometry (MC-ICPMS). The Tl abundance measurements utilise the isotope dilution (ID) technique. About 50 ml of seawater or river water, with ∼150 to 500 pg of Tl, are spiked with a 203Tl tracer and thallium is then separated from the sample matrix using a single anion-exchange column. The isotope compositions of spiked samples are measured by MC-ICPMS using either admixed Pb or Pt for mass bias correction. Replicate analyses of three natural water samples with Tl contents of 3 to 10 pg/g displayed external reproducibilities (1 S.D.) of 0.2% to 1.5%. The determination of Tl isotope compositions requires a minimum of 5 ng of Tl, equivalent to about 0.5 to 1.5 l of seawater or river water. Separation of Tl is achieved with a two-step anion-exchange procedure that generates Tl separates that are essentially Pb-free and that display very low overall matrix contents. The Tl isotope compositions are determined by MC-ICPMS using admixed NIST SRM 981 Pb for the mass discrimination correction. With these techniques, replicate analyses of a seawater and a river water sample displayed an external precision (2 S.D.) of about ±0.1‰. A detailed study was carried out to identify possible sources of systematic error. These investigations indicate that the Tl stable isotope data are not biased by blanks, chemical fractionation during laboratory handling, mass spectrometric errors, spectral interferences, matrix effects, or use of an unsuitable method of mass bias correction. Therefore, the Tl isotope data can be assumed to be accurate, to within the stated uncertainties. Analyses of the international seawater standard NASS-5 were carried out, to provide a reference for future Tl isotope studies. This sample was found to have a Tl concentration of 9.37±0.02 pg/g and a Tl isotope composition of ε 205Tl=-5.0±1.0 (ε 205Tl is the deviation of the 205Tl/ 203Tl isotope ratio of a sample from the NIST SRM 997 Tl isotope standard in parts per 10 4). © 2004 Elsevier B.V. All rights reserved.